Propranolol significantly reduced DNA polymerase Î² expression in patients with essential tremor - Kandemir, Nefise; Kenanoglu, Sercan; Gultekin, Murat; Gokce, Nuriye; Akalin, Hilal; TaÅŸÃ§Ä±oÄŸlu, Nazife; Mirza, Meral; Koseoglu, Emel; Dundar, Munis (Faculty of Medicine, Universitas Trisakti, 2021)
Background Essential tremor (ET) is the most common movement disorder. Propranolol is a first-line medication for ET. We aimed to evaluate the effect of propranolol on the expression of poly (ADP-ribose) polymerase 1 (PARP1) and DNA polymerase beta (POLB) genes, which are known to be related to neurodegenerative diseases, in patients with ET. MethodsThirty-five healthy volunteers and thirty-five patients followed up with essential tremors were included in a non-randomized control experimental study. Expressions of PARP1 and POLB genes were compared between the control group and the patient group. In addition, pre- and post-treatment gene expression levels and Fahn-Tolosa-Marin tremor scale values of the patient group were compared after 8 weeks of propranolol treatment. The Wilcoxon rank and Mann Whitney U tests were used to analyze the data. ResultsAt baseline, PARP1 expression was significantly lower in the ET group than in the control group. (p<0.001). POLB gene expression was significantly higher in the pre-treatment ET group than in the controls (p<0.05). There was no significant difference in PARP1 expression levels before and after 8 weeks of propranolol treatment. POLB gene expression was significantly higher in the pre-treatment group than in the post-treatment group (p<0.001). ConclusionPropranolol significantly decreased POLB gene expression but there was no significant difference in PARP1 gene expression levels in the patient group, after 8 weeks of propranolol treatment.